THE EFFECT OF CONTEXT IN EAP WRITING: A COMPARATIVE ANALYSIS OF ORGANIZATION IN DOCTORAL DISSERTATION ABSTRACTS - Serhat Inan (Journal of Languages for Specific Purposes, 2019)
In EAP (English for Academic Purposes) writing pieces such as articles, theses, and dissertations; convincing the reader to read the rest of the written material is of high importance. The literature presents several models to follow while writing abstracts. Based on this, the current study investigated the textual, organizational and rhetorical structures of the Ph.D. dissertation abstracts written in the Turkish and American contexts. The structures of abstracts were analyzed based on Hyland’s (2000) model for writing abstracts. Additionally, the author presence markers and hedging devices used in the abstracts were investigated. A comparative analysis of EAP writing examples from the two contexts -Turkish and American- revealed that there exist observable differences in terms of abstract writing especially in the organizational structures and the use of hedging devices. The results of the study suggested that in both contexts there is a need to reconsider academic writing education. To be clearer writing abstracts should be handled more carefully by the professors of academic writing instruction.